A Instilling Tolerance Character Values Through Modules Materials of My Country Indonesia for Grade IV Elementary School - Utami, Cindy Prasetya; Yulianti, Yulianti; Sulistyowati, Prihatin (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
The aim of the research is to develop interesting teaching materials for the My Country Class IV Elementary School Pancasila Education module based on the character of tolerance, able to help foster student interest, and the material is easy for students to understand so that students are able to apply the character of tolerance in everyday life. Research and Development (R&D) research method with the 4D development model. The research subjects were the class teacher and 13 fourth grade elementary school students. Data analysis involves qualitative and quantitative descriptive analysis. The research results indicate that a Tolerance Character Based Module that is feasible, practical and efficient has been obtained. Feasibility = 91% with the type